1962
DOI: 10.1111/j.1550-7408.1962.tb02573.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytology of Cold Induced Transformation of Octogenic Reproductive Cysts to Resting Cysts in Colpoda maupasi*

Abstract: SYNOPSIS. Octogenic reproductive cysts are transformed into resting cysts when returned to optimal temperature following prior exposure to cold (5°C) for at least 36 hours. In the cold, the reproductive process ceases and macronuclei revert to the interphase condition. Transformation to resting cysts is synchronous. Induced encystment is accompanied by excessive macronuclear extrusion and is associated with a loss in division potential, resulting in no division, or 1 or 2 divisions in the induced resting cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1964
1964
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…With reference to this issue, Diaz et al, 2003 suggested that cell division must be completed before cells undergo encystment in C. minima. However, observations by Padons, 1962 andMartín-González et al, 1994, in which the 2-cyst was also observed in C. maupasi and C. inflata, contradict the above view. These observations support the traditional idea that dividing vegetative cells can undergo resting cyst formation (Foissner, 1993).…”
Section: Discussionmentioning
confidence: 87%
“…With reference to this issue, Diaz et al, 2003 suggested that cell division must be completed before cells undergo encystment in C. minima. However, observations by Padons, 1962 andMartín-González et al, 1994, in which the 2-cyst was also observed in C. maupasi and C. inflata, contradict the above view. These observations support the traditional idea that dividing vegetative cells can undergo resting cyst formation (Foissner, 1993).…”
Section: Discussionmentioning
confidence: 87%
“…Pattersoniella vitiphila Foissner, 1987 produces normal and giant morphs but never showed cannibalistic behavior (Foissner, 1987). The giant formation is also found in other groups of ciliates such as the peniculine Lembadion bullinum (Kuhlmann, 1993;Kopp and Tollrian, 2003); the colpodeans Colpoda cucullus (Foissner, 1993), C. maupasi (Padnos, 1962), Ottowphrya magna (Foissner et al, 2002), and Platyophryides latus (de Puytorac et al, 1992); the tetrahymenids Glaucoma ferox (Foissner, 2013), G. reniformis, andG. scintillans (McCoy, 1975); and the heterotrichids Blepharisma americanum, B. japonicum, and B. undulans (Giese, 1938;Nilsson, 1967;Schorr and Boggs, 1974;Foissner and O'Donoghue, 1990).…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, in our two strains of C. influtu, these nuclear abnormalities d o not occur. As pointed out by Padnos [37] and Penn [38] if the encystment induction occurs rapidly enough, some division cysts become resting cysts.…”
Section: General Morphology Of Vegetative Cellsmentioning
confidence: 99%